Spontaneous Pneumomediastinum due to Anti-Melanoma Differentiation-Associated Protein 5 Requiring a Bilateral Lung Transplant - Amrit Singh Jhajj; James Hok Shun Yeung; Fergus To (Case Reports in Rheumatology)
Anti-melanoma differentiation-associated protein 5 (anti-MDA5) is a subset of dermatomyositis associated with respiratory complications, in which rapidly progressive interstitial lung disease (RPILD) is commonly cited, and spontaneous pneumomediastinum (SPM) is a rare complication. In medical literature, aggressive immunosuppressive therapy has been the mainstay of anti-MDA5-associated SPM management. Here, we report the first MDA5 case with SPM which was successfully treated with a double-lung transplant. We present a 48-year-old male who presented with multiple constitutional symptoms such as fevers, weight loss, malaise, and arthralgias, in association with erythroderma over the ears and fingers. Imaging of the chest demonstrated peripheral airspace disease, and myositis-specific serology returned positive for anti-Jo1 (medium-positive), anti-Ro52 (high-positive), and anti-MDA5 (weak-positive) autoantibodies. Therefore, the patient was begun on immunosuppressive therapy as the leading diagnosis included autoimmune myositis, possibly antisynthetase syndrome with interstitial lung disease (ILD). A year later, the patient presented with progressive shortness of breath, widespread macular erythematous facial rash, and new erythematous ulcerations over the fingertips. Imaging demonstrated a new SPM at this juncture. As the patient’s respiratory status continued to decline despite the use of immunosuppressive agents, a double-lung transplant was performed. Therefore, we propose that lung transplantation should be considered early in MDA5-SPM.